Saccharomyces Cerevisiae and Pichia Pastoris Optimize NH4NO3 by 50 % in Solanum Lycopersicum Preventing N2O Release. - Prof. Juan Manuel Sánchez Yáñez (International Journal of Pollution: Prevention & Control, 2024)
In agriculture, the unregulated application of NH4NO3 for healthy growth of Solanum lycopersicum is associated in the soil with the denitrification of free NO3- (nitrate), with an increase in N2O, a greenhouse gas, that contributes to global warming, loss of soil fertility. An ecological option to avoid denitrification that releases N2O as other environmental problems is to inoculate S. lycopersicum seeds with endophytic yeasts that promote plant growth, such as Saccharomyces cerevisiae and Pichia pastoris, that increase the uptake of reduced doses of NH4NO3. In this sense, the purpose of this work was to analyze the response of S. lycopersicum to P. pastoris and S. cerevisiae at a dose of 50% NH4NO3. The experiment in a greenhouse, was made in agricultural soil, with a low level of nitrogen available, for the plant. Endophytic yeast were isolated flowers, from wild plants with beneficial activity, for domestic plants were used. To analyze the response of S. lycopersicum to P. pastoris and S. cerevisiae, a randomized trial was used: S. lycopersicum uninoculated with the yeasts: a) irrigated with water only, b) fed with 100% NH4NO3; 3 treatments of S. lycopersicum at 50% NH4NO3 inoculated with: c) S. cerevisiae, d) P. pastoris, e) S. cerevisiae + P. pastoris, and 6 repetitions: The following were considered as response variables: the germination of S. lycopersicum, at the seedling level: plant height (PH) and root length (LR), as well as aerial and radical fresh weight (AFW/RFW) and dry weight: aerial and radical (ADW/RDW). Numerical results were validated with ANOVA/Tukey P<0.05% The main results showed, a better positive response of S. lycoperiscum to P. pastoris at 50% NH4NO3; than with S. cerevisiae or the combination of both. Due to the ability of endophytic yeasts, to invade at the beginning of the formation of the root system, in germination, then in root development, that improved phenology and biomass at the seedling level. This positive effect of this yeasts on S. lycopersicum supports, that they converted organic compounds, from the roots into phytohormones, that maximally increased the uptake of NH4NO3 to 50%, which in the soil, prevents the generation of N2O, the loss of fertility and contamination of surface or underground water, due to excess free nitrogen fertilizer.
Keywords: Endophytic Yeasts; Global Warming; Nitrogen Fertilizer; Plant Growth Promoting Microorganisms; soil